Dampak Demam K-Pop Terhadap Gaya Hidup Dan Konsumsi Remaja Di SMA Swasta Primbana Medan - Irmawaty Tambunan; Naia Rencani Suci; Enggis Br Siagian; Elfretty Br Sitanggang; Yuni Melati Simare-mare (BADAN PENERBIT STIEPARI PRESS, 2024)
K-POP (Korean K-POP) is a southern populer music Korea that is very popular around the world, including Indonesia. Its fans come from all walks of life, including high school students such as those at SMA Swasta Primbana Medan. Usually, K-pop fans, especially teenagers, tend to be fanatical fans who imitate the behaviour of their idols. This study aims to examine the influence of K-Pop South Korea behaviour of its fans, especially students of SMA Swasta Primbana Medan. This study uses a qualitative approach method that focuses on observations, questionnaires, and documented descriptive data. According to the results of this study, the influence of K-POP fever on student behavior can be devided into two types: positive and negative. Positive advantages include a wide range of knowledge, a strong desire to learn, mastering foreign languages, a wide network of friends, high creativity, good cooperation with others fans, and saving habits. The negative impact is that teenagers tend to buy K-Pop idol merchandise, such as albums, posters, and clothes. They often spend time in fantasies, lose concentration on education, often stay up late, prefer to interact in cyberspace, have many enemies, and are very obsessed with their idols. This research shows that K-Pop fever has a significant influence on teenagers' lifestyle and consumption. Education and assistance from parents and teachers are needed so that teenagers can enjoy K-Pop wisely and responsibly.